NCRP Claims Six Studies Support LNT But They Show No-Effect to At Least 100 mGy - K. Chaplin (Dose-Response)
NCRP Commentary-27 reaffirmed Linear No Threshold (LNT) as the basis for radiation protection and listed six studies with “strong support” for LNT. This paper looks critically at these six studies and shows that they do not support LNT in the dose range of 0-100 mGy. These studies typically admit to no increase in cancer risk at significant dose levels. More importantly this paper shows that these studies assume LNT from the outset, underestimate uncertainty, ignore confounding factors, have biased control groups, and underestimate dose.